Hugo J. Verani, De la vanguardia a la posmodernidad: narrativa uruguaya (1920-1995). Trilce, Montevideo, 1996; 238 pp. - Corral, Rose (El Colegio de México, 2017)
Se reseñó el libro: De la vanguardia a la posmodernidad: narrativa uruguaya (1920-1995).